Comparison and convergent validity of five Mediterranean dietary indexes applied to Brazilian adults and older adults: data from a population-based study (2015 ISA-Nutrition): a critical analysis - Cho, Jane; Shah, Vrushank; Lo, David (Journal of nutritional science (Cambridge), 2023)
[...]data acquisition and research is necessary from multiple regions of the world and draw reliable conclusions on adherence to the Mediterranean diet at a global level. [...]the study excluded individuals with chronic alcoholism, however, they did not rule out individuals with substance abuse disorders, eating disorders and mental health conditions that would affect one's lifestyle. [...]socioeconomic status of individuals and social determinants to food access may impact dietary choices and impact adherence to the Mediterranean diet.